Steam engraving optimization of graphitic carbon nitride with enhanced photocatalytic hydrogen evolution. (November 2018) - Chen, Zhou; Yu, Xiang; Zhu, Qiuhui; Fan, Tingting; Wu, Qiuling; Zhang, Lizhong; Li, Jianhui; Fang, Weiping; Yi, Xiaodong
Abstract: Graphitic carbon nitride (g-C3 N4 ) has been extensively investigated as an efficient photocatalyst for water splitting. However, the intrinsic drawbacks of low surface area and poor charge separation efficiency seriously limit its practical applications in photocatalytic hydrogen evolution. Here, we designed an efficient nanorod-C3 N4 photocatalyst by a versatile and scalable steam engraved protocol, which can produce higher surface area, enhanced crystallinity, reduced lattice defects, as well as meliorative energy band configuration. The engraved C3 N4 exhibited a remarkably longer lifetime of charge carriers and a much higher photocatalytic hydrogen production rate than the pristine C3 N4 . The specific activity of the engraved C3 N4 (87 μmol g −1 h −1 cm −2 BET ) is 10.4 times higher than that of pristine C3 N4 . Graphical abstract: A steam-engraved method was used to construct rod C3 N4 with higher surface area, reduced lattice defects, enhanced crystallinity, faster carriers transport and higher photo-drived hydrogen generation performance. Image 1